ANALISIS DAN PERANCANGAN USER INTERFACE PADA APLIKASI REPARATION MENGGUNAKAN METODE GOAL DIRECTED DESIGN - Ruslim, Henderson; Munir, Abdul; Surasa, Hendra (KHARISMA Tech, 2024)
This research aims to redesign the user interface of the Reparation application, a motorcycle repair service in Makassar, using the Goal-Directed Design (GDD) method. Data collection was carried out through interviews and questionnaires with 20 users, and the data was processed using the System Usability Scale (SUS). The initial test obtained an average SUS score of 46.375 with a "Not Acceptable" rating. The second test used a new design prototype, which achieved an average score of 84.5 with an "Acceptable" rating. These results indicate an improvement in interface quality from the "Poor" category to "Excellent". With an average score of 84.5 in the second test, the new design has met the standard average SUS of 68. Thus, the prototype design using GDD has successfully met user needs and produced an attractive and user-friendly interface.